2008
DOI: 10.1159/000129666
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation over the Right Dorsolateral Prefrontal Cortex Disrupts Digit Span Task Performance

Abstract: The digit span task measures the maintenance of information in short-term memory, and is one of the most widely used tests in clinical and experimental neuropsychology. Functional imaging studies have suggested a role of the right dorsolateral prefrontal cortex (DLPFC) in digit span performance. It remains unclear however, whether activation of this area is critical for task performance. Using repetitive transcranial magnetic stimulation (rTMS) over the right DLPFC in a sham-controlled design, we tested the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 47 publications
2
32
0
3
Order By: Relevance
“…attentional resources, relative to those involved in forward recall. The basic effects of 2-back indicate a role for the central executive in encoding short sequences of verbal information (e.g., Aleman & van 't Wout, 2008;Baddeley et al, 2009), but this was no larger for backward than for forward recall. Experiment 1 further revealed that performing a visuospatial task during encoding did not impair backward recall, relative to forward recall, suggesting that it does not particularly rely on visuo-spatial resources either.…”
Section: Discussionmentioning
confidence: 91%
“…attentional resources, relative to those involved in forward recall. The basic effects of 2-back indicate a role for the central executive in encoding short sequences of verbal information (e.g., Aleman & van 't Wout, 2008;Baddeley et al, 2009), but this was no larger for backward than for forward recall. Experiment 1 further revealed that performing a visuospatial task during encoding did not impair backward recall, relative to forward recall, suggesting that it does not particularly rely on visuo-spatial resources either.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, poorer performance on a task reflecting attentional capacity and maintenance of information in short-term memory (Digit Span scores) was the only significant neuropsychological deterioration over time in MCI-V cases. A direct role of the dorsolateral prefrontal cortex in this task has been demonstrated by reversible disruption of this area using repetitive transcranial magnetic stimulation [31]. In this regard, with the criteria used to define our MCI-V patients [7], frontal lobe dysfunction appears to be the core cognitive signature defining the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Hoshi et al [14] conducted an NIRS study and reported that activation of the right dorsolateral prefrontal cortex (DLPFC) is related to performance in the digit span backward task. A previous repetitive transcranial magnetic stimulation study has suggested that the right DLPFC plays a crucial role in the performance of the digit span task [18] . Nevertheless, it has not yet been clearly established whether the right DLPFC plays a crucial role during the performance of this task.…”
Section: Introductionmentioning
confidence: 98%
“…Hoshi et al [14] studied activation of regions of the DLPFC and observed that half of the subjects in their study exhibited greater activation of the right DLPFC whereas the other half exhibited greater activation of the left DLPFC. In the study of Aleman and Wout [18] , the left DLPFC was not examined; this suggests that it may be involved in the digit span task. Furthermore, the sample size of the latter two studies was very small; therefore, further studies are required to clarify the involvement of the DLPFC in the digit span task.…”
Section: Introductionmentioning
confidence: 99%